2017
DOI: 10.3389/fnbeh.2017.00205
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Rewarded Response Inhibition in Youth at Risk for Problematic Alcohol Use

Abstract: Risk for substance use disorder (SUD) is associated with poor response inhibition and heightened reward sensitivity. During adolescence, incentives improve performance on response inhibition tasks and increase recruitment of cortical control areas (Geier et al., 2010) associated with SUD (Chung et al., 2011). However, it is unknown whether incentives moderate the relationship between response inhibition and trait-level psychopathology and personality features of substance use risk. We examined these associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 59 publications
(87 reference statements)
2
23
0
Order By: Relevance
“…We found that greater externalizing scores were associated with poorer correct response rate in the antisaccade task. This result is consistent with our previous findings within a subset of the current sample (Tervo-Clemmens et al, 2017), and supports theories relating disinhibitory phenotypes of substance use risk with poor response inhibition (Iacono et al, 2008;Young et al, 2009). We further sought to investigate how the relationship between inhibitory control limitations and substance use risk changes developmentally.…”
Section: Substance Use Risk Factors and Developmental Improvements Insupporting
confidence: 90%
See 4 more Smart Citations
“…We found that greater externalizing scores were associated with poorer correct response rate in the antisaccade task. This result is consistent with our previous findings within a subset of the current sample (Tervo-Clemmens et al, 2017), and supports theories relating disinhibitory phenotypes of substance use risk with poor response inhibition (Iacono et al, 2008;Young et al, 2009). We further sought to investigate how the relationship between inhibitory control limitations and substance use risk changes developmentally.…”
Section: Substance Use Risk Factors and Developmental Improvements Insupporting
confidence: 90%
“…To this end, it has been suggested that diverging developmental trajectories of inhibitory control and other higher-order cognitive functions may increase vulnerability to problematic substance use (Casey et al, 2008, Steinberg, 2005, by way of early substance use experimentation (Johnston et al, 2018) and individual differences in psychiatric symptoms (Paus et al, 2008) that frequently co-occur with problematic substance use (Kreuger et al, 2002;Hussong et al, 2011). Supporting this perspective, recent work from our group has demonstrated that substance use risk factors, specifically externalizing psychopathology and impulsivity, are associated with poor inhibitory control and cortical activation differences among adolescents during an antisaccade task (Tervo-Clemmens, et al, 2017). However, it remains unclear whether certain periods of development are more sensitive to inhibitory control limitations associated with substance use vulnerability and if at-risk youth follow different trajectories of neurocognitive development.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations